Deoxyribonuclease I Activity, Cell-Free DNA, and Risk of Liver Cancer in a Prospective Cohort. Issue 4 (21st February 2019) - Golonka, Rachel M; Yeoh, Beng San; Petrick, Jessica L; Weinstein, Stephanie J; Albanes, Demetrius; Gewirtz, Andrew T; McGlynn, Katherine A; Vijay-Kumar, Matam
Abstract: Background: Circulating cell-free DNA (cfDNA) is a proposed latent biomarker for several cancers, including liver cancer. Deoxyribonucleases (DNases) facilitate the timely and efficient degradation of cfDNA, leading us to hypothesize that DNase I and/or II might be a more sensitive early biomarker than cfDNA. To test this hypothesis, a study was conducted in a large, prospective cohort. Methods: A nested case-control study (224 liver cancer case patients and 224 matched control subjects) was conducted in a cohort of Finnish male smokers, followed from baseline (1985–1988) to 2014. The associations among DNase I activity, cfDNA, and the risk of liver cancer were assessed using multivariable-adjusted conditional logistic regression. Results: DNase I activity, whether measured as radius (mm) or as units per milliliter, was statistically significantly associated with increased risk of liver cancer ( P trend <.01). DNase I activity in the highest quartile was associated with a greater than threefold risk of developing liver cancer (DNase I activity radius >2.7 mm, hazard ratio [HR] = 3.03, 95% confidence interval [CI] = 1.59 to 5.77; DNase I activity >2.72 units/mL, HR = 3.30, 95% CI = 1.64 to 6.65). The strength of this association was not substantially altered by exclusion of cases diagnosed within the first five years of follow-up or those with hepatitis C virus (HCV) infection. In contrast, cfDNA and DNase II was not statistically significantly associated with risk of liver cancer. Conclusions: DNase I activity was a superior latent biomarker of liver cancer than cfDNA. These findings advance the goal of developing a means to detect liver cancer years well before the development of clinical manifestations.